Financial and institutional reforms for an entrepreneurial society - Claire Economidou; Luca Grilli; Magnus Henrekson; Mark Sanders (Research Institute of Industrial Economics (IFN), 2018)
In this paper, we introduce a special issue of Small Business Economics on Financial and Institutional Reforms for an Entrepreneurial Society in Europe. There are many reasons for Europe to want to make the transition to a more entrepreneurial society. And for decades now, policy makers are trying to bring that transition about with variations on the "educate, deregulate and finance"- approach to entrepreneurship. We argue that more fundamental reforms are required to improve the entrepreneurial ecosystem and bring about this transition. We then discuss the twelve contributions that pertain to five different facets of the entrepreneurial ecosystem. The first two papers address the most fundamental institutional foundations of the ecosystem. The next three papers discuss the (lack of) access to knowledge and incentives to start innovative entrepreneurial ventures. That is followed by three papers that focus on the institutions that (fail to) channel financial resources to such ventures and two papers that analyze the relevance of labor market institutions. The special issue concludes with two papers investigating how the interplay of institutions and productive entrepreneurship results in economic growth.
Keywords: D02; L26; O38; O43; P11; 330; Entrepreneurship; Institutions; Reform; European Union; Innovation